2021
DOI: 10.3390/ijerph182312347
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Responses and Perceived Relative Harm Mediate the Effect of Exposure to Misinformation about E-Cigarettes on Twitter and Intention to Purchase E-Cigarettes among Adult Smokers

Abstract: There is a gap in knowledge on the affective mechanisms underlying effects of exposure to health misinformation. This study aimed to understand whether discrete emotional responses and perceived relative harm of e-cigarettes versus smoking mediate the effect of exposure to tweets about the harms of e-cigarettes on Twitter and intention to purchase e-cigarettes among adult smokers. We conducted a web-based experiment in November 2019 among 2400 adult smokers who were randomly assigned to view one of four condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…like, share), and emotions produced by the message (results presented elsewhere). 15 , 16 After exposure, participants completed post-test measures of knowledge and harm perceptions. They then answered questions on smoking behavior, prior e-cigarette misinformation exposure, social media use and demographic characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…like, share), and emotions produced by the message (results presented elsewhere). 15 , 16 After exposure, participants completed post-test measures of knowledge and harm perceptions. They then answered questions on smoking behavior, prior e-cigarette misinformation exposure, social media use and demographic characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…share, like) tweets that e-cigarettes were just as or more harmful than smoking, 15 we also found that affective responses and perceived relative harm following exposure to misinformation about e-cigarette harms may mediate the relationship with intention to purchase e-cigarettes. 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twitter, a real-time microblogging platform with a generous data availability policy for academic research, has been widely used to understand public perceptions of, and activism on, the health risks of consumer products. Past studies have focused on e-cigarettes (Liu et al, 2021), dietary supplements (Wang et al, 2021), and genetically modified organisms (Jun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%